Source of Information and Its Linguistic Actualization in Modern Information Cognitive Situation - V. Ramantova , Olga; V. Stepanova, Nataliia (International Journal of Psychosocial Rehabilitation, 2020)
This study focuses on the dissemination of information and various substantiation in the conditions of modern mass communication. Namely, the problems of this paper are to describe the main semantic and structural features of information transmission in media space as a communicative process and to identify ways to linguistically represent the information source in modern English-language mass media as a fundamental marker of rumor messages and as a determinant of various aspects of the transmitted information. The study touches upon the linguistic specifics of the ways to generate and transfer information, as well as reveals some patterns in the transmission of unconfirmed or insufficiently truthful information. The study involved semantic-structural and communicative analyses of the material of this paper (news articles selected from the leading English-language Internet sources) to describe the structure of the information cognitive situation in which information is spread regarding mass media communication. Continuous sampling of texts, as well as semantic-cognitive and lexicosemantic analyses, described and classified the most frequent cases of the author's reference to a non-specific source of information and more detailed circumstances in terms of linguistics. The carried out analysis proves the possible relation between the cognitive nature of the meaning and communicative pragmatic factors.